Dinamika Pelestarian Budaya Tarian Gobuk Desa Nagur Kabupaten Serdang Bedagai - Mely Putri Almanda; Erna Erna; Suriya Ningsi; Sahroni Sahroni; Muhammad Habibul Amin; Muhammad Hamzah; Mhd. Tarmizi; Rudiyanto Rudiyanto; Eka Yusnaldi (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
This article examines the culture of the Gobuk dance in the Nagur village area, Tanjung Beringin District, Serdang Bedagai. This article discusses the causes of the disappearance of the Gobuk dance in Nagur Village, and reviews a bit of the history of the dance. This research method uses historical research with a cultural approach. This method aims to describe events or events in the past. The data that the authors get comes from the results of observations and interviews with several informants. The main sources of this research are interviews with several community leaders, the players and dancers of the gobuk dance. In addition, the authors also uses other additional sources in the form of books, journals, and other scientific works, as the main data reinforcement. This Gobuk dance is believed to be able to heal people who are sick. However, not everyone is able to perform the dance with the intention of curing disease, while those who are able to use this dance as a source of treatment are only those who have bloodlines that are part of the dance. However, according to the development of the times, this dance is increasingly losing its existence, especially in the Nagur Village area. Some of the factors that make the existence of the dance fade, namely, the lack of interest of the younger generation due to the development of an increasingly modern era. They think that the dance is not interesting and is considered ancient. The lack of art activists, especially the gobuk dance, has made the dance lost or never performed again in Nagur Village.